Análise espacial e temporal da precipitação, do material particulado e da radiação global em municípios paulistas - Castro, Silvia Garcia de [UNESP] (2015)
This study aimed to Evaluation of spatial and spatiotemporal analysis of precipitation, particulate matter and global solar radiation, as well as their relations on the amount of land available global radiation in the period from 2011 to 2013 in some counties. This work aims to analyze some cities where sugarcane production takes place, at the north and northeast of the State of São Paulo (Presidente Prudente, Ribeirão Preto, Araçatuba, São José do Rio Preto and Bauru), as well as industrialized cities of Jacarei and Santos, respectively in the region of valley and coastline. We used data hourly, daily and monthly particulate matter (PM10) and global radiation provided by CETESB and daily and monthly data from the aerosol optical deph (AOD550) obtained by the Terra satellite. The global radiation data obtained from CETESB, with hourly and monthly temporal resolution were compared to the data and images provided by geostationary satellite (GOES) and modeled by GL Model. The volume of precipitation allowed to infer the conditions of cloudiness and linking pluviose and concentration of the local particulate matter, as well as their relation to the available solar radiation. The additional variables, use and occupation of land and sugar cane burning, facilitated the understanding of spatial differences identified, caused by human activities and environmental factors. The precipitation also has shown the cloudy conditions during the analysis period, and linking pluviosity and concentration local particulate matter, as well as their relation to the available solar radiation. The concentration of particulate matter showed no relevance on the average amount of solar radiation available in the analyzed period, however the monthly and daily variability of the solar resource available has shown the need of further assessment of the impact of particulate matter (PM10) ... (Complete abstract click electronic access below)